2021
DOI: 10.1088/1361-6528/abe439
|View full text |Cite
|
Sign up to set email alerts
|

High-k erbium oxide film prepared by sol-gel method for low-voltage thin-film transistor

Abstract: In this work, high-dielectric-constant (high-k) erbium oxide(Er2O3)film is fabricated using the spin coating method, and annealed at a series of temperatures (from 400 °C to 700 °C). The effect of annealing temperature on the microstructural and electrical properties of Er2O3 nanofilm is investigated. To demonstrate the applicability of the Er2O3 film, the indium oxide (In2O3) thin film transistor (TFT)-based amorphous Er2O3 dielectric film is fabricated at different temperatures. The TFT-based EO-600 shows a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Tests of the groundwater samples showed that the pH value of all groundwater samples was greater than seven, making the groundwater alkaline [37][38][39][40]. The pH value of the strongest alkaline groundwater samples reached 11.52, and 74% of the groundwater samples showed a pH value of over 9 (Figure 7).…”
Section: Analysis and Discussionmentioning
confidence: 98%
“…Tests of the groundwater samples showed that the pH value of all groundwater samples was greater than seven, making the groundwater alkaline [37][38][39][40]. The pH value of the strongest alkaline groundwater samples reached 11.52, and 74% of the groundwater samples showed a pH value of over 9 (Figure 7).…”
Section: Analysis and Discussionmentioning
confidence: 98%
“…Further, in high operating voltages, the reaction rates increase, and with a large amount of product water, the cell is prone to flooding phenomenon. 2633 The flooding in PEM fuel cells increases the transport resistance of the reactants to the active sites causing performance deterioration, energy losses, and reduction in the durability of the materials. 34 Flooding in gas channels of PEMFCs has been studied experimentally and numerically with in-situ and ex-situ visualizations by transparent channels and single/multi-phase one/two/three-dimensional steady-state mathematical models.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, researchers used a two-phase process to separate the sulfate reduction process from the methane production process to eliminate the impact of SRB on MPB, which makes the process complicated and expensive. With the in-depth research on SRB and the development of anaerobic reactors, researchers and engineers are increasingly interested in using some modern new high-efficiency anaerobic reactors to treat high-sulfate wastewater [5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%